Modelisation de I' emboutissage des tissus de fibres de verre par Ia methode des elements finis - Cherouat, A. Hakim; Gelin, Jean-Claude; Boisse, Philippe; Sabhi, Hamid (European Journal of Computational Mechanics, 1995)
The glass fiber fabric shaping process before resin transfer moulding (RTM) is the first stage for manufacturing of reinforced composite structures. A finite element modelling of the process is proposed. The finite element simulation model is based on a discrete summation of the mechanical behaviour of each thread and on a surfacic model for the glass fabric deformation and is well suited for modelling prefonning and deep drawing of glass fiber fabrics. A particularly efficient formulation is proposed in the case where the finite element mesh is structured by thread directions. Comparisons between simulations and experiments prove the efficiency of the proposed approach.